ANALISIS PEMAHAMAN MAHASISWA TERHADAP METODE PENELITIAN DALAM MENYUSUN TUGAS AKHIR PADA MATA KULIAH METODOLOGI PENELITIAN - Irianto (Manajemen Pendidikan Program Doktor, 2024)
This research aims to analyze students' understanding of research methods in preparing their final assignments in the Research Methodology course. Data collected from 80 final semester students from 2 study programs at the BontangCollege of Industrial Engineering, who were or had completed the Research Methodology course, were used in this research to evaluate students' understanding of research methods in preparing final course assignments. The research results show that students generally understand research methods well. However, theoretical concepts are still difficult touse when preparing a final assignment. In addition, differences were seen in the understanding of students from various study programs, students from study programs that were more familiar with quantitative research tended to have better understanding. These results have significant consequences for the teaching of Research Methodology courses, including the need to increase practical learning about engineering.